Преобразуем выражения, воспользовавшись следующими свойствами степеней:
а^c * b^c = (ab)^c,
(a^b)^c = a^(bc),
a^b * a^c = a^(b + c).
x * x^3 * x * x^7 = x^(1 + 3 + 1 + 7) = x^12.
(-2a)^2 * (-2a) * (-2a)^5 = (-2a)^(2 + 1 + 5) = (-2a)^8 = (-1)^8 * 2^8 = 1 * 2^8 = 2^8.
c^m * c * c^2 * c^(m+1) * c = c^(m + 1 + 2 + m + 1 + 1) = c^(2m + 5).
5 * 125 * 25 = 5 * 5^3 * 5^2 = 5^(1 + 3 + 2) = 5^6.
8 * 32 * 16 = 2^3 * 2^5 * 2^4 = 2^(3 + 5 + 4) = 2^12.
3^n * 27 * 3^(n – 4) * 9 = 3^n * 3^3 * 3^(n – 4) * 3^2 = 3^(n + 3 + n – 4 + 2) = 3^(2n + 1).
а) (2x - 3)(4x + 1) = 8x² - 12x + 2x - 3 = 8x² - 10x - 3
б) (3x - y)(2y - 7x) = 6xy - 2y² - 21x² + 7xy = -2y² + 13xy - 21x²
в) a(a + 4) - (a - 2)(a + 6) = a² + 4a - (a² - 2a + 6a - 12) =
= a² + 4a - a² + 2a - 6a + 12 = 12
г) (1 - 3b)(9b² + 3b + 1) = 9b² - 27b³ + 3b - 9b² + 1 - 3b =
= -27b³ + 1 = 1 - 27b³